Biochemical, urinary, and acid-base profile in cattle treated with maintenance enteral electrolyte solutions containing calcium propionate, propylene glycol or glycerol - Ermita, Pedro Ancelmo Nunes; Viana, Rinaldo Batista; Avanza, Marcel Ferreira Bastos; Teixeira, Raffaela Bertoni Cavalcanti; Silva, José Ricardo Barboza; Monteiro, Lorena Chaves; Costa, Caio Monteiro; Bento, Lucas Drumond; Mendes, Paulo Vinicius da Costa; Ferreira Ermita, Dayana Alersa Conceição; Carvalho, Brenda Ventura Lopes; Moreira, Nadyne Souza; et al. (Frontiers in Veterinary Science, 2022)
Enteral fluid therapy administered in continuous flow through the naso-ruminal route for long periods with electrolyte solutions is safe and effective in cattle. The aim of this study was to carry out a comparative assessment between maintenance enteral electrolyte solutions containing calcium propionate, propylene glycol or glycerol administered in continuous flow in cattle. Six heifers were used and the study was carried out in a 6 × 3 crossover design, in which each animal received three different treatments: enteral electrolyte solution containing calcium propionate (ESCaP), enteral electrolyte solution containing glycerol (ESGly) and enteral electrolyte solution containing propylene glycol (ESPrG). Solutions were administered at a rate of 15 mL kg−1 h−1 for 12 h. Serum and urinary biochemical assessment; urinary volume, pH, and specific gravity; and blood gas analysis were measured at 0, 3, 6, 9, 12, and 24 h. All three enteral electrolyte solutions expanded blood volume and increased urine volume without causing electrolyte imbalances. ESCaP caused mild reversible metabolic alkalosis while the most significant glycemic potential was observed in electrolyte solutions containing propylene glycol (ESPrG) and calcium propionate (ESCaP).